Odontome presenting as fibrotic mass in the upper lip: A rare case report - Shrestha, B; Cho, K J; Lee, J H; Subedi, S (Journal of Chitwan Medical College, 2015)
The extraosseous occurrence of Odontome is rare. Trauma to the tooth bud during its early developmental stages has been proposed as a possible predisposing factor for the origin of odontome. In many cases etiology cannot be identified. Here we report an unusual and rare case of odontome presenting as a fibrotic mass on the upper lip in 32 years old female patient. The authors believe this is the rare documented case of odontome occurring within the soft tissue of upper lip. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12573